Tax Competition When Governments Lack Commitment: Excess Capacity as a Countervailing Threat - Janeba, Eckhard (American Economic Review, 2000)
Tax Competition When Governments Lack Commitment: Excess Capacity as a Countervailing Threat by Eckhard Janeba. Published in volume 90, issue 5, pages 1508-1519 of American Economic Review, December 2000